Consulates, Asmara, Harar and Mega, Ethiopia (formerly Abyssinia): General Correspondence and Registers of Correspondence (Records of the Public Record Office.)
This series contains records from various British consulates in Abyssinia (later Ethiopia). Comprises despatches and correspondence of the consular posts at Mega, 1920 to 1933, and at Asmara from 1947, with registers of correspondence of the Harar consulate, 1899 to 1934.